2016
DOI: 10.1007/s13197-016-2255-3
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical study and antioxidant, antimicrobial and anticancer activities of Melanelia subaurifera and Melanelia fuliginosa lichens

Abstract: The aim of this study was to investigate antioxidant, antimicrobial and anticancerous activity of Melanelia subaurifera and Melanelia fuliginosa. The phytochemical analysis was determined by HPLC-UV method. Antioxidant activity was evaluated by DPPH and reducing power assay while antimicrobial activity was determined by minimal inhibitory concentration. The cytotoxic activity was tested using MTT method. The method for quantification of 2'-O-methyl anziaic acid and lecanoric acid in these lichens using RF-HPLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 24 publications
2
27
0
Order By: Relevance
“…Compared to bacteria, fungi are more resistant due to the more complex structure of the cell wall [3]. Similar to this research, the acetone extract of the lichen P. acetabulum and its major compound norstictic acid were previously tested for anti-proliferative activity towards HT29 cells [20].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Compared to bacteria, fungi are more resistant due to the more complex structure of the cell wall [3]. Similar to this research, the acetone extract of the lichen P. acetabulum and its major compound norstictic acid were previously tested for anti-proliferative activity towards HT29 cells [20].…”
Section: Discussionmentioning
confidence: 78%
“…A great diversity of living organisms can be used for the improvement of human health, such as biologically active components extracted from the plants, mushrooms and lichens [1][2][3]. In searching for new therapeutic alternatives, many different lichen species were investigated, due to significant antiviral, antimicrobial, anticancer, antihyperglycemic, cardioprotective, antiparasitic, anti-inflammatory and antibiotic effects that they have exhibited so far [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these experiments, antibacterial effect was observed against the both Gram ‐positive and Gram ‐negative bacteria but it should be noted that the Gram ‐negative bacteria were more resilient. It has been generally reported that the Gram ‐negative bacteria are more resistant than Gram ‐positive . This resistance is likely, due to the fact that Gram ‐negative bacteria have a wall which itself is surrounded by an outer complex membrane, slowing down the passage of hydrophobic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Lichens and their metabolites are shown to possess antibacterial activity against various pathogenic bacteria including antibiotic resistant bacteria. [9,[32][33][34][35][36][37][38] In this study, we evaluated the potential of H. incana to inhibit Gram-positive and Gram-negative bacteria by agar well diffusion method. The presence of an inhibition zone around the well is an indication of antibacterial potential of extract.…”
Section: Antibacterial Activity Of H Incanamentioning
confidence: 99%